A study on the container yard performance level at Klang port container terminal case study: Klang Port Management Sdn. Bhd. / Hidayatulwahyunah Kamarudin - Kamarudin, Hidayatulwahyunah (1999)
All over the world, in particular for export and import activities, containerisation is a typical modernised mode of carrying goods widely used. Before going into deeper, containerisation is a concept of storing goods into steel frame box. Currently in any transportation development, transport lines prefer to use containerisation concept rather than conventional concept because it has clear advantages such as intermodalism, easy handling door to door concept and flexible. Intermodalism is the concept of transportation that can be handled by all modes of transport. Its is intermodalism because container can be handled by sea, air, rail and road. It is easier handling because its come into standard shape and size. Any type of good can be stored in the container such as refrigerated container, petroleum, general cargo and etc.